Perlindungan Hukum Bagi Anak dari Tindak Pidana Narkotika - Erwin T aroreh; Ara Heppy Koespitasari; Stevana Natasya Maristella Lohonauman (LPPM Universitas Ekasakti Padang, 2023)
Children are the hope of the nation. Children are the next generation, therefore continuous guidance and protection is needed for survival, physical, mental, social growth and development as well as protection from all possibilities that will endanger the child and in the future. Narcotics and other illegal drugs are one of the triggers for the destruction of children. Sometimes children are often the targets of narcotics dealers, because children are still unstable, easily influenced and have the potential to become entangled in the abuse of illegal drugs such as narcotics. Children as drug abusers are only victims. So it is not appropriate for the State to provide punishment by considering the child abuser the same as the actual adult (distributor). As victims, children as drug abusers are obliged to receive protection. Child protection is an effort made to create conditions so that every child can carry out their rights and obligations for the normal development of the child's growth, both physically, mentally and socially.